¿La rapidez o flexibilidad?: Un análisis económico de la ampliación de plazos en el arbitraje - Silva Longobardi, Paula (2020)
One of the great similarities between an ordinary judicial process and arbitration is that both take time. However, in arbitration, unlike in court proceedings, certain measures provided are intended to respond to an adequate use of this resource in the process. In general terms, the current legal standards for granting extensions in arbitration are the equality of arms or opportunities and the reasonableness, both duly recognized in the Peruvian Arbitration Law. In this article, the authors review the sufficiency of this standard from the perspective of an economic analysis for each of the phases of the arbitration process and, in this way, propose its use as an approach for the evaluation of reasonableness when having to decide whether to grant an extension in an ongoing process.